2020
DOI: 10.1111/ggr.12341
|View full text |Cite
|
Sign up to set email alerts
|

High‐Precision Zinc Isotopic Measurement of Certified Reference Materials Relevant to the Environmental, Earth, Planetary and Biomedical Sciences

Abstract: The zinc (Zn) stable isotope system has emerged as a powerful tool for investigating natural and anthropogenic processes of interest to disciplines ranging from the Earth and planetary sciences to biomedical research. In nature, Zn isotopes typically fractionate (66 Zn/ 64 Zn) within the range of-1 and +1 permil (‰), and however, analytical limitations restrict the application of the Zn isotope system. Specifically, there is a lack of well-characterised matrix-matched reference materials covering most Zn isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
28
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 98 publications
14
28
2
Order By: Relevance
“…The δ 66 Zn JMC values of DOLT-4, BCR-414 and BCR-279 were -0.96 AE 0.02‰ (1s), +0.29 AE 0.02‰ (1s) and +0.51 AE 0.03‰ (1s), respectively (Table 3). These values corresponded with the reported values of -1.00 AE 0.01‰ (2s) for DOLT-4, +0.29 AE 0.02‰ (2s) for BCR-414 and +0.49 AE 0.01‰ (2s) for BCR-279 by Druce et al (2020).…”
Section: Precision and Bias Of Cu Zn And Pb Isotopessupporting
confidence: 89%
See 1 more Smart Citation
“…The δ 66 Zn JMC values of DOLT-4, BCR-414 and BCR-279 were -0.96 AE 0.02‰ (1s), +0.29 AE 0.02‰ (1s) and +0.51 AE 0.03‰ (1s), respectively (Table 3). These values corresponded with the reported values of -1.00 AE 0.01‰ (2s) for DOLT-4, +0.29 AE 0.02‰ (2s) for BCR-414 and +0.49 AE 0.01‰ (2s) for BCR-279 by Druce et al (2020).…”
Section: Precision and Bias Of Cu Zn And Pb Isotopessupporting
confidence: 89%
“…These values corresponded with the reported values of −1.00 ± 0.01‰ (2 s ) for DOLT‐4, +0.29 ± 0.02‰ (2 s ) for BCR‐414 and +0.49 ± 0.01‰ (2 s ) for BCR‐279 by Druce et al . (2020).…”
Section: Resultsmentioning
confidence: 99%
“…The RMs MESS-3 marine sediment ( n = 9) and SRM 1566b oyster tissue ( n = 4) were prepared in replicates that followed the complete analytical protocol, i.e., sample digestion, ion-exchange chromatography, and replicated isotopic analyses. The δ 66 Zn JMC value for MESS-3 was +0.26 ± 0.06‰ (2s; n = 9), in line with the previously published value, +0.28 ± 0.02‰ (2s) . Certified reference materials for bivalve tissue matrices for Zn isotope analysis are nonexistent.…”
Section: Methodssupporting
confidence: 88%
“…The δ 66 ZnJMC value for MESS-3 was +0.26 ±0.06‰ (2s, n = 9), in line with the previously published value, +0.28 ± 0.02‰ (2s). 54 Certified reference materials for bivalve tissues matrixes for Zn isotope analysis are inexistent. As an alternative, research groups have reported δ 66 ZnJMC values for reference materials that are commercially available.…”
Section: Zinc Isotope Ratio Determinationsmentioning
confidence: 99%
“…The zinc (Zn) stable isotope system is used to investigate natural and anthropogenic processes in various disciplines like Earth and planetary sciences or biomedical research. For there is a lack of well-characterised matrix-matched RMs, Druce et al (2020) have published Zn isotopic data for eighteen reference materials including many previously uncharacterised RMs. A large study on Cd isotopes with results for rock and soil RMs of different providers covering a range of -0.251 to 0.632& relative to NIST SRM 3108 has been conducted by Liu et al using a MC-ICP-MS technique with double spike correction (Liu et al 2020).…”
mentioning
confidence: 99%